Informal sector and economic development: The credit supply channel - Baptiste Massenot; Stéphane Straub (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The standard view suggests that removing barriers to entry and improving judicial enforcement reduces informality and boosts investment and growth. However, a general equilibrium approach shows that this conclusion may hold to a lesser extent in countries with a constrained supply of funds because of, for example, a more concentrated banking sector or lower financial openness. When the formal sector grows larger in those countries, more entrepreneurs become creditworthy, but the higher pressure on the credit market limits further capital accumulation. We show empirical evidence consistent with these predictions.
Keywords: 330